Peningkatan vo2max atlet sprint 400 meter dengan metode latihan circuit 6 minggu - Maulidin, Maulidin; Mujriah, Mujriah; Rachman, Irna Ningsih Amalia (Jurnal Porkes, 2023)
This study aims to determine the increase in Vo2Max of seprint athletes with the sirciut training method for 6 weeks. The type of research is pre-experiment with the design of the one group pretest-postest design. The population was 20 people and the sample used was 10 people consisting of 6 men and 4 puris, which were determined purvosip. Each sample received circuit training 18 times, with a frequency of 3 times a week. The instrument used to measure V02Max athletes before and after training using the multistage fitness test. Data analysis using anova system. The results of the analysis showed a significant difference where (ρ < 0.05) the average value before treatment was 37.1 ± 5.2 (ml / kg / min) and the average value after treatment averaged 39.4 ± 4.7 (ml / kg / min). The conclusion of this study is that there is a difference that occurs between before and after being treated with circuit training for 6 weeks, and a coach must carefully choose training methods to avoid boredom in athletes, the exercises given are in accordance with muscle contractions in the sport and improve cardiovascular.